Prediction of the Variability of Changes in the Intensity and Frequency of Climate Change Reinforced Multi-Day Extreme Precipitation in the North-Central Vietnam Using General Circulation Models and Generalized Extreme Value Distribution Method - Giang, Pham Quy (Frontiers in Earth Science, 2021)
Flooding of downstream agricultural fields and cities is normally caused by consecutive days of extreme precipitation in upstream areas. As climate change is widely projected to accelerate the hydrological cycle, concerns about the increase in frequency and intensity of extreme precipitation arise. The present study used Pattern Scaling coupled with Generalized Extreme Value (GEV) distribution to calculate changes in multi-day extreme precipitation in the North Central Vietnam in 2050, 2070, and 2090 under three AR5's Representative Concentration Pathways RCP2.6, RCP6.0 and RCP8.5. Twenty long-term historical observation stations in the study area with daily data mostly date back to more than 50 years were employed and 5-day maximum total precipitation was analyzed. The results reveal an agreement among the employed GCMs on an increase in the intensity and a shortening of the return periods of extreme precipitation, with the most reinforced trend occurring under RCP8.5, followed by RCP6.0 and then RCP2.6. This indicates that the risk of associated floods is likely to increase, especially under higher RCPs. Therefore, planning and decision making of durable infrastructure along with flood mitigation strategies to cope with such events are recommended.